Crimes Against the Safety and Integrity of Computer Systems and Data - Ciurea, Stefan Tiberiu (Acta Universitatis Danubius. Juridica, 2025)
This article explores the issue of computer crimes, analyzing how Romanian legislation addresses these offenses in its New Criminal Code. Additionally, it examines the challenges faced by judicial practitioners in resolving IT-related cases. The rapid evolution of cybercrime requires continuous legislative adaptation to effectively combat it. However, Romania has so far primarily reorganized previous legal texts rather than introducing substantial changes. As a result, judicial authorities are able to keep pace with cybercriminals but have yet to achieve the ability to stay ahead of them.